Edge of Battle : Jason Richter #2 - Brown, Dale, 1956- (New York : William Morrow, 2006)
Jason Richter and his high-tech unit Task Force TALON are charged with securing the Mexican border, where a terrorist band has been operating with impunity and enflaming the passions of the population.
Publ Weekly
Libr Journal
Adult.
Adult.
Keywords: Romance; Action & Adventure; War & Military; War fiction; Adventure fiction